ALFA-PRF: a novel approach to detect murine perforin release from CTLs into the immune synapse - Rudd-Schmidt, Jesse A.; Laine, Romain F.; Noori, Tahereh; Brennan, Amelia J.; Voskoboinik, Ilia (Frontiers in Immunology, 2022)
When killing through the granule exocytosis pathway, cytotoxic lymphocytes release key effector molecules into the immune synapse, perforin and granzymes, to initiate target cell killing. The pore-forming perforin is essential for the function of cytotoxic lymphocytes, as its pores disrupt the target cell membrane and allow diffusion of pro-apoptotic serine proteases, granzyme, into the target cell, where they initiate various cell death cascades. Unlike human perforin, the detection of its murine counterpart in a live cell system has been problematic due its relatively low expression level and the lack of sensitive antibodies. The lack of a suitable methodology to visualise murine perforin secretion into the synapse hinders the study of the cytotoxic lymphocyte secretory machinery in murine models of human disease. Here, we describe a novel recombinant technology, whereby a short ALFA-tag sequence has been fused with the amino-terminus of a mature murine perforin, and this allowed its detection by the highly specific FluoTag®-X2 anti-ALFA nanobodies using both Total Internal Reflection Fluorescence (TIRF) microscopy of an artificial synapse, and confocal microscopy of the physiological immune synapse with a target cell. This methodology can have broad application in the ﬁeld of cytotoxic lymphocyte biology and for the many models of human disease.